2011
DOI: 10.1590/s0103-84782011005000040
|View full text |Cite
|
Sign up to set email alerts
|

Germinação de embriões e crescimento inicial in vitro de macaúba

Abstract: RESUMO 50 and 100% of minerals, plus coconut water (0, 50, 100 and 150mL L -1

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 14 publications
1
10
0
3
Order By: Relevance
“…This was evidenced in the current study by the reduced development of roots and stems when the seedlings were grown in the pure MS medium. These results agree with those obtained by Soares et al (2011) where an original MS medium was unfavorable in the development of seedlings of another native fruit tree of the Cerrado, Acrocomia aculeata. Malavolta (2006) explains that any nutrient in excess causes nutritional imbalances that inhibit seedling development, as observed in the present study.…”
Section: Ms Salt Concentration (%)supporting
confidence: 91%
See 1 more Smart Citation
“…This was evidenced in the current study by the reduced development of roots and stems when the seedlings were grown in the pure MS medium. These results agree with those obtained by Soares et al (2011) where an original MS medium was unfavorable in the development of seedlings of another native fruit tree of the Cerrado, Acrocomia aculeata. Malavolta (2006) explains that any nutrient in excess causes nutritional imbalances that inhibit seedling development, as observed in the present study.…”
Section: Ms Salt Concentration (%)supporting
confidence: 91%
“…The predominance of studies evaluating the addition of this liquid endosperm in the culture media are most focused on the in vitro cultivation of orchids. For woody plants using this supplement is still scarce, except for some species, such as Acrocomia aculeata and Hancornia speciosa (SOARES et al, 2011, PINHEIRO et al, 2001.…”
Section: Introductionmentioning
confidence: 99%
“…Under natural conditions, germination process may take one to two years. In light of this problem, zygotic embryo in vitro cultivation is presented as a potential solution (SOARES et al, 2011;BORCIONI & NEGRELLE, 2012). Dormancy break researches have intensified, and currently, in vitro zygotic embryo culture makes pre-germinated seeds available in market for "macaúba" seedling development and growth.…”
Section: Introductionmentioning
confidence: 99%
“…Dormancy break researches have intensified, and currently, in vitro zygotic embryo culture makes pre-germinated seeds available in market for "macaúba" seedling development and growth. SOARES et al (2011) studied germination of in vitro initial growth embryo of "macaúba" and found the highest germination percentage at 60 days.…”
Section: Introductionmentioning
confidence: 99%
“…Essa técnica consiste no isolamento e cultivo asséptico de embriões em meio de cultura visando a superar a dormência de sementes e ou viabilizar para que os embriões sejam utilizados como fonte de explantes (HU & FERREIRA, 1998 (PEREIRA et al, 2006;STEINMACHER et al, 2007;LEDO et al, 2007;BANDEIRA, 2008;SOARES et al, 2011).…”
Section: Introductionunclassified